Local Search Quality: Comment on “Product Quality and Entering Through Tying: Experimental Evidence” - Millet, Fabien Curto; Lewis, Stephen; Stoddart, Paul (Management Science, 2022)
Kim and Luca (2019) consider Google’s grouped results for local businesses (the “OneBox”). They contend that Google made a “strategic decision” to exclude reviews from other platforms (like Yelp) in these results and claim that this led to a quality degradation for search users, based on a randomized controlled trial (RCT) experiment. The purpose of this Comment is to clarify the robustness of Kim and Luca’s characterization of the situation and empirical findings, including in particular with respect to the noise and likely bias resulting from the control benchmark for the RCT experiment being based on a degraded version of Google’s OneBox, rather than the actual version. This paper was accepted by Alfonso Gambardella, business strategy.